Iranian Polymer Journal - Nekoomanesh Haghighi, Mehdi; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Iranian Polymer Journal, a monthly peer-reviewed international journal, provides a continuous forum for the dissemination of the original research and latest advances made in science and technology of polymers, covering diverse areas of polymer synthesis, characterization, polymer physics, rubber, plastics and composites, processing and engineering, biopolymers, drug delivery systems and natural polymers to meet specific applications. Also contributions from nano-related fields are regarded especially important for its versatility in modern scientific development.
Keywords: Polymers; Ceramics; Glass; Composites (Materials).; Composite materials; Polymer Sciences; Ceramics, Glass, Composites, Natural Materials; Polymer Sciences